The Composition of Public Expenditure and Growth : A Small-Scale Intertemporal Model for Low-Income Countries - Bayraktar, Nihal (World Bank, Washington, DC, 2012)
This paper presents a small-scale intertemporal model of endogenous growth that accounts for the composition of public expenditure and externalities associated with public capital. Government spending is disaggregated into various components, including maintenance, security, and investment in education, health, and core infrastructure. After studying its long-run properties, the model is calibrated for Haiti, using country-specific information as well as parameter estimates from the literature. A variety of policy experiments are then reported, including a reallocation of spending aimed at creating fiscal space to promote public investment; an improvement in fiscal management that leads to a reduction in tax collection costs; higher spending on security; and a composite fiscal package.